Directional electromagnetic interference shielding of asymmetric structure based on dual-needle 3D printing. (1st March 2023) - Pei, Xiaoyuan; Liu, Guangde; Shi, Haiting; Yu, Rongrong; Wang, Shuo; Liu, Shengkai; Min, Chunying; Song, Jianan; Shao, Ruiqi; Xu, Zhiwei
Abstract: Some special electronic equipment not only need to avoid the interference of external electromagnetic waves (EMWs), but also need to transmit effective signals. Therefore, the development of directional electromagnetic interference (EMI) shielding materials has a great prospect. The asymmetric structure, consisting of the porous magentic rGF (reduced graphene oxide and Fe3 O4 ) layer and the dense electrical conductivity rGM (reduced graphene oxide and MXene) layer, was constructed by dual-needle 3D printing technology. After encapsulation and curing with polydimethylsiloxane (PDMS), the rGF/rGM/PDMS composites were prepared. When the ratio of rGF and rGM layers is 6:4, the SE values of rGF-6/rGM-4/PDMS composites are 38.75 dB and 30.79 dB respectively when EMWs are incident on the rGF layer and rGM layer respectively, and the ΔSE of which is about 8 dB. The results showed that the asymmetric structure composed of porous magnetic layer and dense deeply electric conductive layer could generate a special process of "weak reflection-absorption-strong reflection-reabsorption" for incident EMW. At the same time, the simulation results of the waveguide method validated the experimental results, and further explained the directional EMI shielding mechanism of asymmetric structure. For the first time, this work designs an asymmetric structure based on the double needle 3D printing technology, which provides useful inspiration for the structural design and potential application of directional EMI shielding materials. Graphical abstract: Image 1